Presidential Address: The Future of the Past in Canada on the Eve of the Twenty-First Century - Leith, James (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1995)
AbstractIn the past half-century, the historical profession in Canada has broadened its attention significantly beyond the political, diplomatic, and military concerns that were dominant as recently as the 1950s. This came about in particular by three challenges: from Marxists who insisted on the study of history from the bottom up and on the importance of class and class conflict; from feminists, who focussed attention on the history of women and gender relations; and from scholars who shifted the historical study of politics from political systems to political cultures. Other methodological innovations also helped broaden the study of history, most noticeably the use of statistics in historical analysis.This "opening" of the profession has, however, made it more sectarian and fractious. Moreover, the attention of historians continues to be paid to the western world and is now largely focussed on the last two-and-a-half centuries. A longer and much wider view of human history is necessary. Accordingly, the paper briefly discusses examples drawn from daily life - paper, food, flowers, and the environment - as evidence of the global nature of history and of the importance of the longue durée in it. The paper concludes by arguing that it is essential for historians to enlargen their conception of the past, for by examining much earlier times and very different cultures, we may come to recognize what is distinctive or peculiar about ourselves as well as others. Such imaginative travels through space and time provide a deeply humanizing and liberating experience.